2010
DOI: 10.1073/pnas.0912617107
|View full text |Cite
|
Sign up to set email alerts
|

In situ assembly of macromolecular complexes triggered by light

Abstract: Chemical biology aims for a perfect control of protein complexes in time and space by their site-specific labeling, manipulation, and structured organization. Here we developed a self-inactivated, lock-and-key recognition element whose binding to His-tagged proteins can be triggered by light from zero to nanomolar affinity. Activation is achieved by photocleavage of a tethered intramolecular ligand arming a multivalent chelator head for high-affinity protein interaction. We demonstrate site-specific, stable, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 32 publications
1
40
0
4
Order By: Relevance
“…Perturbations using small chemicals 4 or lightsensitive molecules 5,6 are now exploited to understand biological functions 7 . For instance, gating activity by light-switchable interactions (allostery, scaffolding) using optogenetic tools has become a promising approach for localizing signalling pathways 8,9 .…”
mentioning
confidence: 99%
“…Perturbations using small chemicals 4 or lightsensitive molecules 5,6 are now exploited to understand biological functions 7 . For instance, gating activity by light-switchable interactions (allostery, scaffolding) using optogenetic tools has become a promising approach for localizing signalling pathways 8,9 .…”
mentioning
confidence: 99%
“…Obwohl ursprünglich für die Aufreinigung rekombinanter Proteine entwickelt, [1][2][3][4] kommt diese Methode in zahlreichen anderen Anwendungen zum Einsatz. Diese Technik ermçg-lichte zum Beispiel die spezifische Immobilisierung von Proteinen auf Proteinchips, [5,6] die Inkorporierung aktiver Proteine in Nanomaterialien [7,8] und Oberflächen, [9,10] die Markierung von Proteinen mit Fluorophoren [11][12][13][14] und die spezifische Konjugation von Biomolekülen mit Proteinen. [15][16][17] Im Komplex [18][19][20] sowie die Bildung kovalenter Bindungen durch photochemische [21,22] (oder weniger spezifische) [23,24] [28,29] Außerdem werden Komplexe von bioaktiven Liganden mit substitutionsinerten Metallen als Prodrug eingesetzt, die erst nach dem Eindringen in die Zelle aktiviert werden.…”
unclassified
“…Protein microarrays have been fabricated using a variety of ligand pairs, including azide-alkyne click chemistry, double-stranded DNA hybridization, and avidin-biotin interactions. An appealing feature of the Grunwald et al (3) study is the use of the widely available Histag system, where an immobilized metal ion recognizes an oligo-His affinity tag introduced into a protein using genetic engineering. The Ni-NTA (nitrilotriacetic acid)·oligo-His complex can be reversed by the addition of imidazole or EDTA.…”
mentioning
confidence: 99%
“…Ideally, protein microarrays could be prepared via iterative light-based assembly (9), because light offers the advantage that the domains of individual proteins that can be fabricated are in the size range of 10-50 μm (related to the near-UV light wavelength), much smaller than the physical delivery techniques (spotting, jetting) that can be iterated. Until the methodology of Grunwald et al (3), such a capability had not been demonstrated.…”
mentioning
confidence: 99%